Voci - Del Buono, Cat (FedOA - Federico II University Press, 2023)
Annotation: in order to correctly display the file use the player downloadable at the URL: https://heyzine.com/flip-book/66fbb742b3.html The Voci digital book is based on the 2022 exhibit that took place in Naples, Italy. With a Fulbright Scholar Award, and the collaboration of the University Federico II and the Assessorato alle pari opportunità del Comune di Napoli, art-based research culminated in the creation of a video installation. Filmed interviews were presented on 14 video monitors creating a multi-layered conversation about domestic violence, particularly during the Covid-19 lockdowns in Italy. It included the voices of survivors of domestic violence and the advocates who help them, psychologists, researchers, and abusers themselves. The immersive installation was accompanied by a panel discussion that was open to the public.